Improvement of intake work-main transmission line-sand trap system in aqueduct of Calarca, Quindio (Revista de Investigaciones Universidad del Quindío, 2010)
The water intake area of the aqueduct system in the town of Calarcá (Department of Quindío), located in the uppermost zone of Santo Domingo river, was constantly out of service due to the high flow of solid material carried by this mountain river, which is characterized by a turbulent flow regime. The Company MULTIPROPOSITO DE CALARCA S.A. ESP which is in charge of providing, among other services, the aqueduct service in the town, requested University of Quindío, through Extension Office of Faculty of Engineering and with support of research group CIDERA, to analyze the current hydrologic and hydraulic situation, and perform the studies that allow to determine the actions to be taken in the intake area and the upgrading of every unit and related elements in intake work, main transmission line and sandtrap.
Keywords: Aqueduct System; Intake Structure; Main Transmission Line